China's Emergence in the World Economy and Business Cycles in Latin America - Ambrogio Cesa-Bianchi; M. Hashem Pesaran; Alessandro Rebucci; TengTeng Xu (Inter-American Development Bank (IDB), 2011)
This paper investigates how changes in trade linkages between China, Latin America, and the rest of the world have altered the transmission of international business cycles to Latin America. Evidence based on a GVAR model for five large Latin American economies shows that the long-term impact of a China GDP shock on the typical Latin American economy has increased by three times since the mid-1990s, while the long-term impact of a US GDP shock has halved, while the transmission of shocks to Latin America and the rest of emerging Asia GDP (excluding China and India) has not changed. These changes owe more changes in China's impact on Latin America's traditional and largest trading partners than to increased direct bilateral trade linkages boosted by the decade-long commodity price boom. These findings have important implications for both Latin America and the international business cycle.
Keywords: C32; E32; F44; O54; 330; Konjunkturzusammenhang; Internationale Wirtschaftsbeziehungen; Lateinamerika; China; Finanzkrise; Wirtschaftskrise; Welt